A STUDY OF SUPERIORITY COMPLEX IN CHRIS GARDNERS THE PURSUIT OF HAPPYNESS - ALAYDRUS ZARKASY, KEMAL (LANGUAGE HORIZON, 2019)
This research is taking objective to reveal the causes and impacts of superiority complex behavior which overwrites Chris Gardner that is appeared in Chris Gardner?s The Pursuit of Happyness. The objectives are the psychological aspect of the main character which is also the author of the novel and his internal conflict. Thus, this study is analyzing the psychology of the main character using individual psychology by Alfred Adler. Based on it, the formulated problems are; (1) how does superiority complex is being portrayed in Chris Gardner?s The Pursuit of Happyness? (2) what are the causes of Chris Gardner?s superiority complex? And (3) what are the impacts of Chris Gardner?s superiority complex toward his personality? To analyze the data, this study is using qualitative approach which the instruments are taking from documentation (quoting), and the analysis is critical interpretation, and also reporter the finding of the study. The novel tells about the life of Chris Gardner who loves in struggling from superiority complex in his life. He lived in a small apartment and spent his money for buying franchise to sell bone scanner which sis made a big problem in his life. He cannot make money by working as a bone scanner salesman. His wife was sick of Gardner?s job and forced Chris Gardner to walk away from home and her life. Until someday Chris met a man with luxury Ferrari and he is a stockbroker. Since that day, Chris Gardner wanted to be a stockbroker in order to make his life better and makes his son happy. In the end of the story, Chris succeed to be a staff in a Dean Witter firm and soon he was been the found of the investment firm Gardner Rich in 1987. Keyword: Chris Gardner, Internal Conflict, Struggle, Superiority Complex.